Model Simulasi Sistem Antrian dalam Rantai Pasok Industri Batu Bara untuk Optimalisasi Jaringan Logistik - Abdullah, Yoga Rahmad; Nuha, Hilyatun; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The increasing domestic demand for coal necessitates greater efficiency in logistics systems and supply chains, particularly for mining companies such as PT. Mahakam. This study aims to design a queue system simulation model to optimize the company’s logistics performance by applying queueing theory and utilizing the ARENA simulation software. The research evaluates key variables such as waiting time, queue length, and the utilization rate of unloading facilities, in an effort to address demurrage issues arising from logistical inefficiencies. A mixed-method approach combining quantitative and qualitative data analysis was employed, using both primary and secondary data collected from PT. Mahakam’s logistics operations between January and June 2024. Simulation results indicate that logistics effectiveness can be improved through adjustments in the number of operators, enhancement of unloading equipment, and more structured management of the distribution flow. This research is expected to serve as a foundation for developing simulation-based logistics models in the coal industry and to contribute to the practical application of queueing theory in industrial settings.